2008
DOI: 10.3934/amc.2008.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Groups from cyclic infrastructures and Pohlig-Hellman in certain infrastructures

Abstract: In discrete logarithm based cryptography, a method by Pohlig and Hellman allows solving the discrete logarithm problem efficiently if the group order is known and has no large prime factors. The consequence is that such groups are avoided. In the past, there have been proposals for cryptography based on cyclic infrastructures. We will show that the Pohlig-Hellman method can be adapted to certain cyclic infrastructures, which similarly implies that certain infrastructures should not be used for cryptography. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…This shows that our new definition is indeed a generalization of the notion of a one-dimensional infrastructure as in Section 3 or [Fon08].…”
Section: Conversely If Repmentioning
confidence: 72%
See 2 more Smart Citations
“…This shows that our new definition is indeed a generalization of the notion of a one-dimensional infrastructure as in Section 3 or [Fon08].…”
Section: Conversely If Repmentioning
confidence: 72%
“…This interpretation goes back to Lenstra's work in [Len82]. See also [Fon08] for an earlier treatment of (abstract) one-dimensional infrastructures. The infrastructure essentially offers two operations:…”
Section: One-dimensional Infrastructuresmentioning
confidence: 86%
See 1 more Smart Citation
“…However, as the infrastructure is not a group, it is not immediately obvious that similar techniques would work in this setting. F o n t e i n [13], [14] showed that the Pohlig-Hellman algorithm can indeed be adapted to solve the infrastructure discrete logarithm problem, and that, consequently, only hyperelliptic curves whose regulator has a large prime divisor should be used for cryptographic purposes. In particular, Fontein described a concept called f -representations, an explicit method of embedding the elements of the infrastructure into a cyclic group of order R that preserves distances.…”
Section: Recent Resultsmentioning
confidence: 99%
“…Finally, the infrastructure setting was generalized completely by F o n t e i n in [13], [14]. In addition to independently showing how to embed the infrastructure of a real hyperelliptic curve into a group, Fontein interprets the infrastructures of essentially any function field in a very broad context using Arakelov theory and very reasonable basic assumptions.…”
Section: History and Related Workmentioning
confidence: 99%